Sporenbildung bei Bacillus subtilis: Masse oder Klasse? - Bischofs-Pfeifer, Ilka (Biospektrum, 2020)
Recent timelapse microscopy studies suggest that endospore forming bacteria encounter a quantity-quality tradeoff: Bacillus subtilis can either make more or better spores. Natural isolates employ different life-cycle strategies that are beneficial under different revival conditions. These findings have implications for our understanding of the ecology and evolution of sporulating bacteria and their use in biotechnological applications.